Christ And Culture Revisited - "Carson, D. A." ("Grand Rapids, Mich. :")
"Includes bibliographical references and indexes. How to think about culture : reminding ourselves of Niebuhr -- Niebuhr revised : the impact of biblical theology -- Refining culture and redefining postmodernism -- Secularism, democracy, freedom, and power -- Church and state -- On disputed agendas, frustrated utopias, and ongoing tensions."
Keywords: "CHRISTIANITY AND CULTURE.;NIEBUHR, H. RICHARD (HELMUT RICHARD), 1894-1962.;CHRIST AND CULTURE."